Investment Preference of Generation Z Between Physical and Digital Gold Based on Factors of Trust, Risk Perception, and Social Influence - Putri, Chindi Oktafiani; Pangestuty, Farah Wulandari (Contemporary Studies in Economic, Finance and Banking, 2026)
As digital natives, Generation Z has great potential in adopting digital-based investment instruments. However, the tendency to choose physical gold persists amid the growing popularity of digital gold investments, highlighting the need for an analysis of the factors influencing gold investment preferences among Generation Z. This study aims to analyze the effects of trust, risk perception, and social influence on Generation Z's probability of choosing digital gold investments over physical gold. The study uses a quantitative approach with a survey method through questionnaires targeting Generation Z individuals who have an interest or experience in gold investment. The sample was determined using purposive sampling, and the data were analyzed using binary logistic regression. The results of the study indicate that trust and social influence act as driving factors for digital gold investment preferences, while risk perception acts as an inhibiting factor. These findings confirm that Generation Z's gold investment preferences are influenced by psychological and social factors, and have implications for the development of digital gold investment services and educational strategies.